Efisiensi Dan Efektivitas Rantai Nilai Produk Hortikultura: Sebuah Kajian Komprehensif - Herlambang, Tedy; Musriati, Titik (Universitas Panca Marga, 2022)
Simple on a paper, but complex in reality, that is horticulture value chain. It is a social-ecological system formed by bio-physic and social factors. The activities and nodes in the value chain involving processes and various dimensions social, economic, politic, geography, governance, institutional, science and environmental with diverse outcomes. Therefore, any efforts aimed at increasing the efficiency and effectiveness of horticulture value chain cannot be undertaken partially. This article presents a comprehensive framework on how to increase such value chain in Indonesia and its possible applications. Keywords: efficiency, effectiveness, horticulture value chain